Serious Adverse Events Following COVID 19 Vaccination in India: A Retrospective Study - Sruthikrishna Punathukandi; Jayakrishnan Thayyil; Meera S. Nair; Ahana Salam (Preventive Medicine: Research & Reviews, 2025)
Introduction: The aim of this study was to identify the type and detail the serious adverse events following COVID-19 vaccination in India. Materials and Methods: The descriptive study was conducted by extracting the data from the website by the Ministry of Health and Family Welfare, Government of India https://shorturl.at/imwJY. The variables analysed were types of vaccines, types of SAEFI, thromboembolic (TE) events, neurological manifestations and consistent causal association as per the World Health Organization. Data were entered into MS Excel and analysed using the SPSS software version 25. Results: Out of the total 1.9 billion doses of COVID-19 vaccines, 1527 cases of SAEFI were reported. Among these, 51.7% were coincidental and 30.8% were associated with vaccination. All the allergic reactions (58), anaphylaxis (50), TE events (342) and Guillain–Barre syndrome (41) had consistent causal association. Out of the 598 deaths, 2% of deaths had consistent causal association. In comparison of exposure to Covaxin, Covishield had high odds of death (odds ratio [OR] =1.5; 95% confidence interval [CI] =1.11–2.07), acute febrile illness (OR = 2.07; 95% CI = 1–4.3), TE events (OR = 1.58; 95% CI = 1.08–2.31) and cardiovascular events (OR = 2.03; 95% CI = 1.32–3.13). Conclusions: Compared to other countries, similar types of SAEFIs were reported from India but at a lower rate.